Striatal dopamine synthesis capacity in autism spectrum disorder and its relation with social defeat: an [(18)F]-FDOPA PET/CT study - Schalbroeck, Rik (Transl Psychiatry, 2021)
Alterations in dopamine signalling have been implied in autism spectrum disorder (ASD), and these could be associated with the risk of developing a psychotic disorder in ASD adults. Negative social experiences and feelings of social defeat might result in an increase in dopamine functioning. However, few studies examined dopamine functioning in vivo in ASD. Here we examine whether striatal dopamine synthesis capacity is increased in ASD and associated with social defeat. Forty-four unmedicated, non-psychotic adults diagnosed with ASD and 22 matched controls, aged 18–30 years, completed a dynamic 3,4-dihydroxy-6-[(18)F]-fluoro-L-phenylalanine positron emission tomography/computed tomography ([(18)F]-FDOPA PET/CT) scan to measure presynaptic dopamine synthesis capacity in the striatum. We considered unwanted loneliness, ascertained using the UCLA Loneliness Scale, as primary measure of social defeat. We found no statistically significant difference in striatal dopamine synthesis capacity between ASD and controls (F(1,60) = 0.026, p = 0.87). In ASD, striatal dopamine synthesis capacity was not significantly associated with loneliness (β = 0.01, p = 0.96). Secondary analyses showed comparable results when examining the associative, limbic, and sensorimotor sub-regions of the striatum (all p-values > 0.05). Results were similar before and after adjusting for age, sex, smoking-status, and PET/CT-scanner-type. In conclusion, in unmedicated, non-psychotic adults with ASD, striatal dopamine synthesis capacity is not increased and not associated with social defeat.